Treatment of Radiation Lesions with Mesenchymal Stem Cells - Já. Lakota (Вестник войск РХБ защиты)
Acute radiation syndrome (ARS) is an acute illness caused by exposure to a high dose of ionizing radiation. ARS is the deterministic effect of radiation exposure of the whole body or a significant body volume (partial body irradiation) above a threshold dose of about 1 Gy (gray). Radiation accidents, such as those in Chernobyl (1986) and Fukushima (2011), or the possible use of nuclear weapons during the hostilities or terrorist attacks, can lead to the massive development of ARS in humans.   The aim of the work is to introduce a new method of post-radiation treatment – the use of allogeneic mesenchymal stem cells (MSCs).   Materials and methods. The information contained in specialized scientific journals that are freely available and accessible through the global Internet was studied.   Discussion of the results. In the scenario of mass exposure of the population, when from several tens (hundreds) to millions of people can be irradiated, the transfusion of hematopoietic stem cells traditionally used in such cases would be impossible. MSCs can possibly differentiate into specialized cells, that is, turn into cells of various organs and tissues or induce such kind of regeneration. For practical use, there are two main sources of their isolation and reproduction ex vivo – bone marrow and adipose tissue. To date, it has been shown that MSCs derived from adipose tissue can be effective in mitigating the effects of acute radiation illness. Intravenously applied MSCs are migrating mainly to the bone marrow and are partially restoring its function. Deep anatomical structures are also involved in local radiation injuries: bone, muscles, nerves, blood and lymphatic vessels and skin. There is a strong body of evidence suggesting the «repair effect» of MSCs when used to treat such lesions. This is because MSCs can induce the repair and regeneration of the anatomical structures which they are locally applied, possibly by the paracrine effect. The main advantage of allogeneic MSCs over autologous ones is their logistical accessibility. They can be produced in advance in quantities and stored frozen. After thawing, the cells must be cultured for at least 48 hours in humidified incubators with the addition of 5 % CO2.   Findings. Treatment of MSCs should be started as soon as possible after radiation exposure. Rescue of damaged hematopoiesis in the bone marrow can be achieved by multiple intravenous administration of up to 1 million (106) freshly prepared allogeneic MSCs/kg body weight. Locally (around and in the irradiation area), the dose of MSCs may be lower – 20 million cells. Repeated topical application should be carried out at intervals of two to four weeks. Subsequent surgical reconstruction should be performed by an experienced surgeon and in a specialized center with concomitant topicalapplication of MSCs.